Site‐Selective C–H Amidation of 2‐Aryl Quinazolinones Using Nitrene Surrogates. Issue 46 (28th September 2020) - Kim, Saegun; Jeoung, Daeun; Kim, Kunyoung; Lee, Seok Beom; Lee, Suk Hun; Park, Min Seo; Ghosh, Prithwish; Mishra, Neeraj Kumar; Hong, Suckchang; Kim, In Su
Abstract : The site‐selective modifications of quinazolinones constitute a pivotal topic in drug discovery and material science. Herein, we describe the rhodium(III)‐catalyzed C–H amidation of 2‐aryl quinazolin‐4(3 H )‐ones with a range of nitrene surrogates including dioxazolones, organic azides, and N ‐methoxyamides. Complete site‐selectivity and functional group tolerance are observed. Notably, the large‐scale reaction and late‐stage functionalization highlight the synthetic potential of the developed protocol. Combined mechanistic investigations elucidate a plausible reaction mechanism of this process. Abstract : The site‐selective C–H amidation of 2‐aryl quinazolin‐4(3 H )‐ones with dioxazolones under rhodium(III) catalysis is described. Gram‐scale reaction, late‐stage C–H functionalization, and synthetic transformations highlight the potential of the developed method.